Special Job Exchange Strategies for Enhancing Graduate Employability in Vocational High Schools Center of Excellence in Yogyakarta and Central Java - Suprap, Suprap; Sayuti, Muhammad; Santosa, Budi; Biddinika, Muhammad Kunta; Susanto, Harry Agus; Hasanah , Noviatun (Journal of Vocational Education Studies, 2024)
This study aims to examine the strategy of the Special Job Exchange (BKK) of the Central Vocational Education Center of Excellence (SMK PK) in Yogyakarta and Central Java in increasing the absorption of graduates in the world of work. The research method used is qualitative descriptive with data collection techniques through interviews with the Principal and Chairman of BKK from 10 PK Vocational education selected through purposive sampling. Data analysis uses Miles and Huberman's interactive model with the help of NVIVO version 12 Plus software. The results of the study show that BKK's main strategy includes cooperation with industry, development of job preparation programs, strengthening students' soft skills and mentality, and the implementation of tracer studies. The challenges faced include students' interests and mentality that need to be improved, limited resources, data and communication management, program synchronization, expansion of industry networks, parental support, and improvement of the quality of graduates. This study concludes that BKK has an important role in increasing the absorption of vocational school graduates, but still faces various challenges that require a comprehensive and collaborative approach to overcome them.